A case of Sjogren’s syndrome presenting as hypokalaemia secondary to renal tubular acidosis - M., Savitha; Vidyasagar, Sudha; Murali, Sudhinder; Srinivasan, Sahana (International Journal of Research in Medical Sciences, 2025)
Renal tubular acidosis (RTA) is a known but relatively rare presentation of Sjogren’s syndrome. It requires a high level of clinical suspicion to be diagnosed. We report a 38-year-old female who presented with respiratory arrest that was later found to be caused by hypokalemia secondary to renal tubular acidosis. Further work up proved a diagnosis of Sjogren’s syndrome. The patient improved with correction of electrolytes and hydroxychloroquine. This case highlights the importance of consideration of Sjogren’s syndrome as a probable cause of RTA as renal complications of Sjogren’s syndrome have a good prognosis if identified and treated promptly.